THE EFFECTIVENESS OF WATCHING RUN BTS ON WEVERSE APPLICATION FOR VOCABULARY MASTERY: Bulan Permata Maulana*, Aswir, Mutiarani - Bulan Permata Maulana; Aswir; Mutiarani (Samudra Publisher, 2024)
The purpose of this study is to assess how effective RUN BTS videos on the Weverse app work as a substitute for vocabulary enrichment activities. This study used an experimental pre-test-post-test control group design using a quantitative methodology. One senior high school class from Jakarta, Indonesia served as the research sample. For four weeks, the experimental class received treatment by watching two RUN BTS episodes on the Weverse app. Pre-test and post-tests totalling twenty questions were used to gather data. This is predicated on the pre-test mean score of sixty and the post-test mean score of seventy-nine points. Observing RUN BTS on Weverse has an impact on learning outcomes, based on the results of the rise in learning outcomes